Factores explicativos de la no adherencia al tratamiento antihipertensivo. Estudio multivariado - Sagástegui Sánchez, Sheyla Gimena (2019)
OBJECTIVE: To identify the explanatory factors of non-adherence to antihypertensive treatment. MATERIAL AND METHOD: Retrospective analytical observational study. 365 hypertensive patients who met the selection criteria were studied. Adherence was assessed with the Morisky-Green Test, and variables related to socioeconomic factors, health system, disease, treatment and patient were valued. Bivariate analysis was performed to identify associated and risk factors, and logistic regression analysis to construct the multivariate model. The validity of the model was estimated using the area under the receiver operating characteristics curve (AUC-ROC). RESULTS: The factors included in the model were: Age (OR = 0.97; 95%CI 0.95-0.99), low level of education (OR=2.4; 95%CI 1.4-4.0), no family support (OR = 2.6; 95%CI 1.5 -4.5), dissatisfaction with medical care (OR = 3.2; 95%CI 1.7-6.2), adverse reactions (OR = 3.4; 95%CI 1.4-8.4), number of drugs for another disease (OR = 0.77; 95% CI 0.64- 0.94) and inadequate level of knowledge (OR = 4.6; 95%CI 2.8-7.8). The AUC-ROC of the model was 0.805. CONCLUSION: The explanatory factors of non-adherence to antihypertensive treatment are: Younger age, low level of instruction, no family support, dissatisfaction with medical care, adverse reactions, inadequate level of knowledge and lower number of drugs for another disease.